Toward a new paradigm in resistance training by means of velocity monitoring: A critical and challenging narrative - González-Badillo, J. J.; Sánchez-Medina, L.; Ribas-Serna, J.; Rodríguez-Rosell, D. (Sports Medicine - Open, 2022)
Key Points - The main limitation of current resistance training practice and methodology fundamentally lies in the necessity to ascertain the degree of effort actually performed by the athlete or practitioner in each training session. The monitoring of repetition velocity contributes decisively to overcoming this limitation.